How to Accurately Delineate Morphologically Conserved Taxa and Diagnose Their Phenotypic Disparities: Species Delimitation in Cryptic Rhinolophidae (Chiroptera) - Chornelia, Ada; Lu, Jianmei; Hughes, Alice Catherine (Frontiers in Ecology and Evolution, 2022)
Systematics and taxonomy are a backbone of all components of biology and ecology, yet cryptic species present a major challenge to accurate species identification. This is especially problematic as they represent a substantial portion of undiscovered biodiversity, and have implications for not only species conservation, but even assaying potential risk of zoonotic spillover. Here, we use integrative approaches to delineate potential cryptic species in horseshoe bats (Rhinolophidae), evaluate the phenotypic disparities between cryptic species and identify key traits for their identification. We tested the use of multispecies coalescent models in species delimitation and in absence of gene flow, we found BPP to be useful in delineating potential cryptic species, in agreement with acoustic differentiation between potential cryptic species. However, using a range of different prior settings (the ratio of population size to divergence times) is crucial to ensure the valid interpretation of species delimitation model. Our results show that around 40% of Asian rhinolophids species are potentially cryptic and have not been described. In order to avoid potential misidentification and allow species to be accurately identified, we identified quantitative noseleaf sella traits and acoustic traits as the most informative traits in delineating between potential cryptic species in Rhinolophidae. This highlights the physical differences between cryptic species are clearer in noseleaf traits which often just qualitatively described but rarely measured. Each part of the noseleaf including the sella, lateral lappets, and lancet furrows play roles in focusing acoustic beams and thus, provide useful characteristics for the identification the cryptic in future studies. Finally, species delimitation for cryptic species cannot rely on genetic data alone, but such data should be used as a complement of other evidence including phenotypic as well as acoustic data, and geographic distribution to ensure accurate species identification and delineation.